Rapid slice excitation without B0 gradients using large array coils - Feng, Ke; Wright, Steven M. (Quantitative Imaging in Medicine and Surgery, 2014)
In a large transmit planar pair phased array with the same power level in each channel, it is shown that controlling the phase shift between neighboring channels can yield different transmit slice thickness. Similarly, variation of the power level can move the slice less or further into the subject for imaging. The technique may be of particular interest as it allows curved slice excitation. These excitation patterns are achieved without complicated RF pulse sequences, i.e., without the use of multi-dimensional RF pulses. Simple simulations based on Biot-Savart law are used to predict the effect of the phase offset and power level variation. Planar and cylindrical formed planar pair coil arrays are both simulated and later built and tested using an MR scanner. The array is flexible and formed around the surface of objects under study, and the excitation is near the surface. Simulation results are compared with actual MRI images with good agreement. This technique is potentially useful for slice excitation in very rapid or ultra-short echo sequences.